Parents Double Wings to the Child - Hilola Safarova Oxunjonovna (Indonesian Journal of Innovation Studies, 2022)
Article by Bukhara poet Samandar Vakhidov "Secret Conversation with Childhood", “Do you remember your childhood”, “ I would like to take the moon as a child”, "Childhood in my dreams",“Uzbek child” which states that childhood is a flawless period of human life.